Can foreign lobbying enhance development ? : The case of tourism in the Caribbean - Rojas, Gabriel V. Montes (The World Bank, 2007)
There exist legal channels for informational lobbying of U.S. policymakers by foreign principals. Foreign governments and private sector principals frequently and intensively use this institutional channel to lobby on trade and tourism issues. The authors empirically study whether such lobbying effectively achieves its goal of trade promotion in the context of Caribbean tourism and it is the first paper to examine the potential for using foreign lobbying as a vehicle for development. They use panel data to explore and quantify the association between foreign lobbying by Caribbean principals and U.S. tourist arrivals to Caribbean destinations. A variety of sensitivity analyses support the finding of a strong association. The policy implications are obvious and potentially important for developing countries